Role of Ratings of Perceived Exertion during Self-Paced Exercise: What are We Actually Measuring? - Abbiss, Chris R.; Peiffer, Jeremiah J.; Meeusen, Romain; Skorski, Sabrina (Sports medicine (Auckland), 2015)
Ratings of perceived exertion (RPE) and effort are considered extremely important in the regulation of intensity during self-paced physical activity. While effort and exertion are slightly different constructs, these terms are often used interchangeably within the literature. The development of perceptions of both effort and exertion is a complicated process involving numerous neural processes occurring in various regions within the brain. It is widely accepted that perceptions of effort are highly dependent on efferent copies of central drive which are sent from motor to sensory regions of the brain. Additionally, it has been suggested that perceptions of effort and exertion are integrated based on the balance between corollary discharge and actual afferent feedback; however, the involvement of peripheral afferent sensory feedback in the development of such perceptions has been debated. As such, this review examines the possible difference between effort and exertion, and the implications of such differences in understanding the role of such perceptions in the regulation of pace during exercise.